Correlation between laser welding sequence and distortions for thin sheet structures. (17th February 2017) - Fahlström, K.; Andersson, O.; Melander, A.; Karlsson, L.; Svensson, L.-E.
Abstract : Thin ultra-high strength steel shaped as 700 mm long U-beams have been laser welded in overlap configuration to study the influence of welding sequence on distortions. Three different welding directions, three different energy inputs as well as stitch welding have been evaluated, using resistance spot welding (RSW) as a reference. Transverse widening at the ends and narrowing at the centre of the beam were measured. A clear correlation was found between the weld metal volume and distortion. For continuous welds there was also a nearly linear relationship between the energy input and distortion. However, the amount of distortion was not affected by a change in welding direction. Stitching and RSW reduced distortion significantly compared to continuous laser welding.